2022
DOI: 10.1002/ijch.202100125
|View full text |Cite
|
Sign up to set email alerts
|

III–VI and IV–VI van der Waals Semiconductors InSe, GaSe and GeSe: A Suitable Platform for Efficient Electrochemical Water Splitting, Photocatalysis and Chemical Sensing

Abstract: Here, we discuss the physicochemical properties of both bulk and nanosheets of III-VI and IV-VI metal chalcogenides and their application capabilities in electrocatalysis, photocatalysis, and gas sensing by combining density function theory with surface-science experiments. In particular, GaSe, InSe, and GeSe are van der Waals semiconductors stable in water media and robust against CO poisoning, which make them suitable candidates for application as low-cost (photo)catalysts in liquid media. Both bulk and exfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 117 publications
(220 reference statements)
0
7
0
Order By: Relevance
“…73−76 However, given the XPS results, it is unlikely that it originates from involvement of a Pr 4+ /Pr 3+ couple, but perhaps through mechanisms like those in GaSe, which undergoes similar changes in its Ga 3d and Se 3d XPS spectra. 77,78…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…73−76 However, given the XPS results, it is unlikely that it originates from involvement of a Pr 4+ /Pr 3+ couple, but perhaps through mechanisms like those in GaSe, which undergoes similar changes in its Ga 3d and Se 3d XPS spectra. 77,78…”
Section: Resultsmentioning
confidence: 99%
“…For Nd 4 Ga 2 Se 7 O 2 , the spectra were much less significantly affected, suggesting only mild surface oxidation. The superior electrocatalytic performance of the Pr member is an interesting result that appears to be observed in other RE -containing catalysts for water splitting, including perovskites and alloys. However, given the XPS results, it is unlikely that it originates from involvement of a Pr 4+ /Pr 3+ couple, but perhaps through mechanisms like those in GaSe, which undergoes similar changes in its Ga 3d and Se 3d XPS spectra. , …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it has been found that introducing QDs to the surface of 2D nanomaterials increases the number of activation sites in 2D materials. As a result, most of the researchers are trying to make ultrasensitive detectors by using such heterojunctions. , There are several articles based on innovative 2D semiconductors, and their heterostructure sensor has been reported in the last few years. The research may have used a specific research design or methodology that has limitations. For example, the research may have relied on self-report measures, which could be subject to biases or may not fully capture the complexity of the phenomenon under investigation.…”
Section: Introductionmentioning
confidence: 99%
“… 1 − 15 These compelling physical/chemical properties of 2D nanomaterials compared to bulk counterparts improve their applicability in various fields of catalysis, nanomechanics, gas sensors, and so on. 2 20 Particularly, the ultrathin nanosheets are most versatile one as nearly all the active atoms of the material lie at the surface of nanosheets maximizing the utility of such atoms. 2 25 Hence, the interaction between the weakly coordinated active surface atoms of the nanosheets and reactant species and the distinctive electronic property arising from 2D effects of nanosheets can tremendously change the activity of ultrathin nanosheets compared to conventional nanosheets/nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrathin two-dimensional (2D) nanomaterials are a class of material endowed with sheetlike nanostructure of atomic thicknesses and high area/thickness aspect ratios. Owing to the geometric confinement in one of the dimensions, they have been attracting a lot of attention as a new generation advanced material with distinctive physical/chemical properties. These compelling physical/chemical properties of 2D nanomaterials compared to bulk counterparts improve their applicability in various fields of catalysis, nanomechanics, gas sensors, and so on. Particularly, the ultrathin nanosheets are most versatile one as nearly all the active atoms of the material lie at the surface of nanosheets maximizing the utility of such atoms. Hence, the interaction between the weakly coordinated active surface atoms of the nanosheets and reactant species and the distinctive electronic property arising from 2D effects of nanosheets can tremendously change the activity of ultrathin nanosheets compared to conventional nanosheets/nanostructures. The synthesis of ultrathin nanosheets from 2D graphene and graphene-type materials with layered structures that are bonded by weak van der Waals force are easy to prepare from their bulk structure. However, achieving ultrathin nanosheets and their assembly of a s...…”
Section: Introductionmentioning
confidence: 99%